2015
DOI: 10.4103/0974-9233.167815
|View full text |Cite
|
Sign up to set email alerts
|

Review of ocular manifestations of nevoid basal cell carcinoma syndrome: What an ophthalmologist needs to know

Abstract: Nevoid basal cell carcinoma syndrome (NBCCS) is a rare, autosomal dominant disorder characterized by multiple basal cell carcinomas (BCCs), odontogenic keratocysts, palmar and/or plantar pits, and ectopic calcifications of the falx cerebri. Myriad ophthalmologic findings are associated with NBCCS, including periocular BCCs, hypertelorism, strabismus, myelinated nerve fibers, and disorders of the retina and retinal pigment epithelium. We performed a literature search in PubMed for articles on the ophthalmologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…27 It has been demonstrated that the inactivation of the PATCH gene may be responsible for the development of fibroglial epiretinal membrane and abnormal ganglion-cell axon myelination. 18 This is also shown by the common recurrence in our NBCCS group of epiretinal membranes and myelinated fibers. PATCH deficient murine models showed dysplastic foci in the retina and abnormal gliotic response further confirming the key role of SHH/PATCHED in glial cells homeostasis.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…27 It has been demonstrated that the inactivation of the PATCH gene may be responsible for the development of fibroglial epiretinal membrane and abnormal ganglion-cell axon myelination. 18 This is also shown by the common recurrence in our NBCCS group of epiretinal membranes and myelinated fibers. PATCH deficient murine models showed dysplastic foci in the retina and abnormal gliotic response further confirming the key role of SHH/PATCHED in glial cells homeostasis.…”
Section: Discussionsupporting
confidence: 63%
“…14 Other common findings in NBCCS patients are hypertelorism, congenital cataract, strabismus, myelinated fibers, retinal hamartoma, optic nerve colobomas, nystagmus and palpebral ptosis. [15][16][17][18] The objective of the present study is to evaluate the integrity of the macular pathways and functionality in NBCCS patients by means of pattern reversal visual evoked potentials (pVEPs). The results obtained were compared with a control group (CG) of healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…NBCCS also predisposes some patients to various low-frequency tumors, such as ovarian fibroma, medulloblastoma, rhabdomyosarcomas, and cardiac fibromas ( 1 ). Ocular anomalies occur in some cases, including strabismus, congenital cataracts, eyelid cysts, myelinated nerve fibers, and pigmentary changes of the retinal epithelium ( 2 ). Multiple organ systems may be affected in NBCCS.…”
Section: Introductionmentioning
confidence: 99%
“…Basal Cell Carcinoma Syndrome is diagnosed with two major criteria or one major plus two minor criteria. The diagnostic criteria of this syndrome are summarized in Box 1 (10). Genetic counselling must be considered.…”
Section: Introductionmentioning
confidence: 99%